Saudis compliant with ethical research guidelines - Nature Research (16552612) (2016)
In 1996, the International Council on Harmonization (ICH) compiled the Good Clinical Practice (GCP) guidelines, describing the responsibilities and expectations of the various participants involved in the conduct of clinical trials. Healthcare professionals in Saudi Arabia were surveyed about their knowledge, perceptions and attitudes towards these ICH-GCP guidelines. The vast majority (85%) had received GCP training, while 97% said they followed GCP guidelines during their clinical trial studies and that GCP-compliant activities improved the quality of clinical research. The study, published in the journal Avicenna , found that although awareness and compliance levels were reportedly high, only 57% of those surveyed said clinical research was a routine part of their clinic’s activities. Also, almost three quarters of the respondents had faced delays in the approval process from institutional review boards and 59% expressed a negative attitude towards this process and review boards’ monitoring and audits of clinical trials. The study surveyed 78 healthcare professionals working at King Abdullah International Medical Research Center and King Abdulaziz Medical City in Riyadh. This represents the first assessment on the knowledge and attitudes of healthcare professionals in Saudi Arabia toward the ICH-GCP guidelines, says the study’s author Nora Al-Nomay from King Saud bin Abdulaziz University. Pharmaceutical companies are becoming increasingly attracted to countries like Saudi Arabia, which are becoming more intent on addressing their citizens’ common health problems. Assessing the implementation of institutional and national ethical guidelines for clinical research is thus particularly important for these companies. A 2003 study conducted in Finland reported that the pharmaceutical industry recognizes the need for GCP training, since poor GCP compliance can lead to an increased workload, extra costs and delays in the critical timeline of drug development. Investigators also believe that poor GCP compliance can affect their relationship with their studies’ sponsors. Poor GCP compliance can also have deleterious effects on the safety of patients. Further research is needed to assess the effectiveness of different strategies for the monitoring and auditing of clinical trials in order to encourage young researchers to employ ethical guidelines, concludes Al-Nomay. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0